An analysis on the classification of financial crises - Yılmaz, Kadir Ünsal (My University, 2010)
Finansal Krizlerin Sınıflandırılması Üzerine Bir Analiz Günümüzde ekonomistlerin son Türkiye krizinde de gördüğümüz üzere krizin türü üzerinde anlaşamadıkları büyük bir sır değil. Bu nedenle de bu çalışmanın amacı, finansal krizlerin türlerini tanımlamak üzere güçlü bir matematiksel model oluşturabilmektir. Bunun için de, çeşitli istatistik veritabanları ve de ilgili bakanlıklardan derlenmiş ve krizlerle bağlantılı olduğu varsayılan birçok makroekonomik ve finansal değişken temel indirgeme metodu olan “Temel Bileşenler Analizi “ metoduyla incelenmiştir. Sonuçlar inceleme yaptığımız değişkenlerin bir finansal krizin türünü belirlemek konusunda elimize yeterli doneyi verebildiğini göstermektedir.

An Analysis on the Classification of Financial Crises It is not the best kept secret that the economists generally can not agree on the type of a crisis for the ones that occur in Turkey. Because of this, the main aim of this study is to create a solid mathematical background on defining the types of financial crises. To do this, many economic and financial data obtained from statistical databases and related ministries, is checked which are supposed to be related with financial crisis, and the main data reduction method :” principal components analysis “ is used. Results showing that, it is possible to conclude with the data used in this work, if a crisis is banking oriented, debt oriented or currency oriented.
Keywords: Finansal Krizler